TRS: System for recommending semantic web service composition approaches - Garg S.K.; Mishra R.B. (My University, 2025)
A large number of semantic web service composition approaches are developed by the research community and one is more efficient than the other one depending on the particular situation of use. So a close look at the requirements of ones particular situation is necessary to find a suitable approach. In this paper, we presents a Technique Recommendation System (TRS) which using a classification of state-of-art semantic web service composition approaches, can provide the user of system with the recommendations regarding the use of service composition approach based on some parameters regarding situation of use. TRS has modular architecture and uses the production rules for knowledge representation. © 2008 IEEE.